THE ROLE OF PENCHAK-SILAT IN THE FORMATION OF THE PSYCHO-PHYSICAL QUALITIES OF THE PERSON (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article discusses combat sports in the modern world, including such a sport as pencak-silat. Theoretical aspects of the formation of psychophysical and personal qualities of athletes in combat sports are revealed.